2019
DOI: 10.1155/2019/8159506
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Prediction of Occupational Diseases in China with Hybrid Algorithm Combing Models

Abstract: Occupational disease is a huge problem in China, and many workers are under risk. Accurate forecasting of occupational disease incidence can provide critical information for prevention and control. Therefore, in this study, five hybrid algorithm combing models were assessed on their effectiveness and applicability to predict the incidence of occupational diseases in China. The five hybrid algorithm combing models are the combination of five grey models (EGM, ODGM, EDGM, DGM, and Verhulst) and five state-of-art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Meanwhile, 160 million workers suffer from occupational diseases with non-fatal work. Losses due to occupational illnesses and deaths due to occupational factors account for 4%-6% of the gross domestic product in related countries and regions in the world [2].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, 160 million workers suffer from occupational diseases with non-fatal work. Losses due to occupational illnesses and deaths due to occupational factors account for 4%-6% of the gross domestic product in related countries and regions in the world [2].…”
Section: Introductionmentioning
confidence: 99%
“…Because of these peculiar properties, ISM excels at solving high-level problems, vis-a-vis cause-root analysis, complex process definitions, or simply a concept. A simple application of ISM, including grouping and sequencing, is used in industrial activities [27].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these considerations, we considered that ISM is a relevant and applicable method to determine the key elements in the musculoskeletal disorders incidence in the instant food industry. Meanwhile, valuable information for controlling and preventing occupational diseases was obtained from predictions of research models [27].…”
Section: Introductionmentioning
confidence: 99%
“…In Sukmak et al's study, two ANN models, namely, radial basis function (RBF) and multi-layer perceptron (MLP) networks, were constructed to predict the monthly visits of anxiety disorder patients [ 3 ]. In Lu et al's study, five hybrid algorithm combing models were assessed and the results showed that the GM-ANN model provided the most precise prediction in forecasting the incidence of occupational diseases in China [ 28 ]. Khaldi et al [ 29 ] found that ANN assisted with EEMD outperformed the benchmarking models for approximation and generalization capabilities, while overcoming the problem of overfitting.…”
Section: Introductionmentioning
confidence: 99%